THE ADDITION TO ISOMETRIC HAMSTRING INCREASES THE WOMAN PATIENT’S LENGTH STEP WITH OSTEOARTHRITIS OF THE KNEE - Sulistinawati, Eny (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 1 (2013): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2013.v01.i01.p01)
Backgaround : The female patients with osteoarthritis of the knee is usually adecrease in length step. It was the morphological changes can be decrease inflexibility, strength, endurance and stability of the muscle and joint. That all canbe decrease the function of capacity, include of there length step. Objective :This research aimed to identifi addition to isometric hamstring increases the woman patient’s length step with osteoarthritis of the knee. Method : Thisresearch is using pre test and post test control group design. Patients wererandomised into two groups : the Control Group (CG) that use ultrasound, TENSand isometric quadriceps is 11 patients. The Experimental Group (EG) that useUltasound, TENS, isometric quadriceps and hamstring is 11 patients too. Result :The result of CG test which using compare means with paired sample t-test,p>0,05 (p=0,249) that mean the intervention in CG is not having significant toincreasing length step. In the result of EG test which using compare means withpaired sample t-test, p<0,05 (p=0,000) that mean the intervention in EG is havingsignificant to increasing length step. The result test researcher using comparemean test with independent sample t-test, p<0,05 (p=0,000), that means there aresignificant different between EG result and CG result. In one tail hypothesis gotresult p<0,05, so it shows that intervention in EG more effective significantly thanCG in to increasing length step to female patients with osteoarthritis of the knee.Conclusion : Addition to isometric hamstring increases the woman patient’slength step with osteoarthritis of the knee.
Keywords: US, TENS, isometrik quadriceps-hamstring, OA, length step.